PENGARUH LATIHAN SMALL SIDED GAMES (SSG) DAN TRIANGLE PASS TERHADAP KETERAMPILAN PASSING STOPING SISWA EKSTRAKURIKULER SEPAK BOLA SDN 02 PENGADANGAN - Rusdiana Yusuf; Adi Suriatno (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Student interest at SDN 02 Pengadangan in playing soccer is quite high, but students have different abilities. For example, passing to a friend is less accurate, passing is too fast or sometimes too slow, making it difficult to combine passes between friends/players. This research aims to determine whether or not there is an influence of small sided games (SSG) training on the passing stopping ability of extracurricular football students at SDN 02 Pengadangan. This research uses quantitative design methods or design using experimental methods. The research design is to use a Two Group Pretest-Protest Design. The results of this research show that there is an influence of small sided games (SSG) training on passing stopping ability. This is proven by the results of data analysis which shows the average value or mean passing and stopping increased from 5.60 to 7.55. Apart from that, the t test results also prove this effect with t test results of 7.870 with a sig value level. 0.03 < 0.05. There is an influence of triangle pass training on students' passing stopping abilities. This is proven by the results of data analysis which shows that the t test results also prove this effect with t test results of 9.788 with a sig value level. 0.01 < 0.05. Triangle pass training has a more significant influence than small sided game training on improving the passing stopping ability of extracurricular soccer students at SDN 02 Pengadangan. This is proven by the results of data analysis which shows that the mean value of the small side games posttest = 61.15 with a t value of -7870.